2020
DOI: 10.1371/journal.pone.0231720
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyposmia distinguishes neuropathologically confirmed dementia with Lewy bodies from Alzheimer’s disease dementia

Abstract: Many subjects with neuropathologically-confirmed dementia with Lewy bodies (DLB) are never diagnosed during life, instead being categorized as Alzheimer's disease dementia (ADD) or unspecified dementia. Unrecognized DLB therefore is a critical impediment to clinical studies and treatment trials of both ADD and DLB. There are studies that suggest that olfactory function tests may be able to distinguish DLB from ADD, but few of these had neuropathological confirmation of diagnosis. We compared University of Penn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 118 publications
2
21
0
Order By: Relevance
“…Olfactory impairment has been demonstrated in a plethora of neurological disorders, including AD, Parkinson’s disease (PD) and DLB [ 8 , 9 ]. Although not currently implemented in the clinic, olfactory assessment has been postulated as a promising tool for the differential diagnosis of AD and DLB [ 10 , 11 , 12 , 13 , 14 ]. Previous clinicopathological studies have shown that olfactory dysfunction is associated with Lewy body pathology in limbic and neocortical regions [ 15 ], and to date, most of the studies have revealed that olfactory deficits are more severe in DLB than in AD [ 8 , 13 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory impairment has been demonstrated in a plethora of neurological disorders, including AD, Parkinson’s disease (PD) and DLB [ 8 , 9 ]. Although not currently implemented in the clinic, olfactory assessment has been postulated as a promising tool for the differential diagnosis of AD and DLB [ 10 , 11 , 12 , 13 , 14 ]. Previous clinicopathological studies have shown that olfactory dysfunction is associated with Lewy body pathology in limbic and neocortical regions [ 15 ], and to date, most of the studies have revealed that olfactory deficits are more severe in DLB than in AD [ 8 , 13 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although not currently implemented in the clinic, olfactory assessment has been postulated as a promising tool for the differential diagnosis of AD and DLB [ 10 , 11 , 12 , 13 , 14 ]. Previous clinicopathological studies have shown that olfactory dysfunction is associated with Lewy body pathology in limbic and neocortical regions [ 15 ], and to date, most of the studies have revealed that olfactory deficits are more severe in DLB than in AD [ 8 , 13 , 14 , 16 ]. However, despite the great attention that has caught in the last decade, the sense of smell is often undermine in the clinical diagnosis, and clinicians rarely test this deficit in patients with suspicion of neurological disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hyposmia is likely to begin at prodromal disease stages as it is present in subjects with incidental Lewy body disease and often predates the appearance of motor features. [1][2][3][4][5][6][7][8] On the contrary, patients with clinically determined progressive supranuclear palsy (PSP) have been reported to have normal olfaction. [9][10][11][12][13] However, there is a lack of studies performed regarding pathological confirmation of disease state.…”
Section: Supporting Datamentioning
confidence: 99%
“…Secondary pneumonias may be more common given that people with DLB often have a pharyngeal-type dysfunction, which results in a high prevalence of silent aspiration. 12 This could contribute to diagnostic difficulty especially in conjunction with anosmia, another symptom commonly associated with DLB, 13 and which is also indicative of COVID-19.…”
Section: Physical Challengesmentioning
confidence: 99%